2013
DOI: 10.1002/pbc.24849
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine responsive megaloblastic anemia: The puzzling phenotype

Abstract: TRMA is a disease of expanding phenotypic spectrum with poor genotype-phenotype correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Oxoglutarate dehydrogenase complex intervenes in the production of succinyl‐coenzyme A, which is the substrate of the enzyme delta‐aminolevulinate synthase 2, an enzyme that catalyzes the first step of the synthesis of the heme group. The role of TPP as a cofactor of this enzyme complex may explain the megaloblastic anemia that is observed in Rogers syndrome …”
Section: Biochemistry Of Thiamine In Humansmentioning
confidence: 99%
“…Oxoglutarate dehydrogenase complex intervenes in the production of succinyl‐coenzyme A, which is the substrate of the enzyme delta‐aminolevulinate synthase 2, an enzyme that catalyzes the first step of the synthesis of the heme group. The role of TPP as a cofactor of this enzyme complex may explain the megaloblastic anemia that is observed in Rogers syndrome …”
Section: Biochemistry Of Thiamine In Humansmentioning
confidence: 99%
“…Megaloblastic changes and the presence of more than 10% sideroblasts in the bone marrow aspiration leads to the diagnosis of TRMA. 11 Beshlawi et al, 5 reported that response to thiamine was variable, hemoglobin level can reach normal values and insulin dose decreased after one month with thiamine therapy (100 mg/ day). Two patients were stopped using insulin after thiamine dose reached 200 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients were stopped using insulin after thiamine dose reached 200 mg/day. 3,5 Alzahrani et al informed that high dose thiamine therapy in TRMA patients can improve the disease symptoms, correct the anemia and reduce or discontinue the need for exogenous insulin. 12 Our patient was diagnosed non-autoimmune diabetes mellitus at age of 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,56 Because deafness was the earliest symptoms diagnosed in the disease, reflecting the fact that hearing loss is more recognizable than anemia and diabetes, the results of newborn hearing tests could aid in the differential diagnosis of SLC19A2 deficiency among patients with PNDM to permit an earlier diagnosis, proper treatment, and less mortality. 52,60,61 It has been shown that despite thiamine treatment, insulin dependency can relapse after adolescence in some SLC19A2-deficient patients. 18,44,45 Considering that thiamine can be passively transported into cells at higher concentration, the reason for disease recurrence is probably the result of relatively insufficient thiamine supplementation (maximum 300 mg daily in the literature; see Table S2) when the patients grew up.…”
Section: Discussionmentioning
confidence: 99%